SURAH AL-QUR’AN DALAM PROSESI PAGELARAN JAMASAN KERIS: Studi Budaya Kejawen dan Budaya Islam di Desa Aeng Tong-Tong Saronggi Sumenep - Roidul Wafa; Faishal Khair; Abd. Mun’em; Abd. Basid (Jurnal Studi Qur'an dan Tafsir, 2025)
The jamasan keris tradition is a cultural heritage of the Javanese and Madurese communities that continues to be preserved by the people of Aeng Tong-Tong Village, Sumenep. This procession is not only understood as the physical maintenance of the keris but also as a form of respect for the spiritual values believed to be contained within the heirloom. In the context of the Aeng Tong-Tong community, this practice has been carried out from generation to generation and has become an important part of the local cultural identity. This study aims to reveal two things: First, how the Qur’anic reception is manifested in the jamasan keris procession. Second, what values are contained within the practice of jamasan. To achieve these objectives, the study employs a qualitative approach with field study methods and reception analysis (reception theory) to explore the meanings embedded in the jamasan keris practice. Data were collected through participatory observation, in-depth interviews, and documentation of the jamasan procession carried out by the community. This research also examines how Qur’anic texts—particularly Surah Yāsin, al-Fātihah, and Āyat al-Kursī—are positioned and interpreted within the cultural ritual structure of jamasan. This theoretical approach allows the researcher to understand the community’s reception of the Qur’an as a sacred text that interacts with local traditions. The study concludes: First, jamasan keris serves as a means of preserving ancestral values as well as spiritualizing the heirloom through rituals considered sacred. Second, the recitation of Qur’anic surahs in the jamasan procession functions as a medium of purification, protection, and reinforcement of spiritual energy. The reception of the Qur’an in this context is not merely textual-normative but has undergone cultural reinterpretation, reflecting a process of acculturation between Javanese mysticism (Kejawen) and Islamic teachings.